GRAMMATICAL ERROR ANALYSIS IN TOURISM OBJECTS INFORMATION OF WEBSITEOF MALANG CITY TOUR - YUDHARAHARJA, ADHITYA PRATAMA (Jurnal Ilmiah Mahasiswa FIB, 2013)
The internet website is widely used to promote tourism objects internationally, especially the English written website. However, information should be well written. Sometimes incorrect tenses or structures of a sentence, which are called error, can cause multiple interpretations to the readers. Related to that, the writer conducted this study to reveal the grammatical errors in tourism object information of Malang City Tour website.This study is a qualitative one, which uses document or content analysis design, because the data were taken from documents or materials of website of Malang City Tour. In data analysis, the writer classified the data by using The result of the study reveals that the errors found mostly belong to misformation errors. The writer found 45% misformation errors, 40% omission errors, 10% addition errors and 5% misordering errors. In addition, the study reveals that the sources of errors mostly happen because of intralingual error. The grammatical errors which are found are in the use of the passive voice and From the results of the study, the writer suggests the next researchers, who are interested in the same topic to broaden this study by analyzing grammatical errors applied in particular objects from others points of view such as the use idiolect in conversation related to the speech style and other theories.   Keywords: Error, Grammatical Error, Tourism Object, WebsiteDulay’s surface strategy taxonomy theory and Richard’s sources of competence error theory.suffixs. In addition, based on source of error, the writer found 92% intralingual errors,and 8% interference errors, but did not find any developmental error.